ANALISIS BUTIR SOAL ULANGAN AKHIR SEMESTER GENAP MATA PELAJARAN BAHASA INDONESIA KELAS X SMA NEGERI 2 KUPANG TIMUR TAHUN AJARAN 2022/2023. - Benu, Desi Sepriana; Margareta, Karus M.; Nitbani, Semuel H.; Nai, Firmina A. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
The main problem in this research focuses on the distribution of levels in the Cognitive domain in the end-of-semester exam questions for class X Indonesian Language at SMA Negeri 2 Kupang for the 2022/2023 academic year. The final even semester test questions for the Indonesian Language subject are used as research data as analysis material to determine the distribution of levels in the Cognitive domain in the questions. This research uses learning evaluation theory according to the views of Slameto (2001) as a reference to determine the distribution of levels in the Cognitive domain in the questions. The method used is descriptive quantitative. The data collection technique in this research uses a collection technique with research data documents which are analyzed and described to obtain research results. The results of this research show that of the 30 question numbers analyzed, it was found that 1 question was at cognitive level C1 (3%), C2 had 18 questions (60%), C3 had 3 questions (10%), C4 had 1 7 questions (24%), C5 amounted to 1 question item (3%) and C6 cognitive level was not distributed in the final semester assessment questions. Based on the analysis results obtained, it can be concluded that these questions are not suitable to be used as test questions and must be revised.